Living wage movements: global perspectives (Abingdon, 2012)
"Living wage activism has spanned time and space, reaching across decades and national boundaries. Conditions generating living wage movements early in the twentieth century have resurfaced in the twenty-first century, only on a global scale: 'sweated' labour, macroeconomic instability, and job insecurity.